Clinical evaluation of a combination therapy of imepitoin with phenobarbital in dogs with refractory idiopathic epilepsy. Issue 1 (December 2016) - Neßler, Jasmin; Rundfeldt, Chris; Löscher, Wolfgang; Kostic, Draginja; Keefe, Thomas; Tipold, Andrea
Abstract Background Imepitoin was tested as a combination treatment with phenobarbital in an open-label mono-centre cohort study in dogs with drug-resistant epilepsy. Diagnosis of idiopathic epilepsy was based on clinical findings, magnetic resonance imaging and cerebrospinal fluid analysis. Three cohorts were treated. In cohort A, dogs not responding to phenobarbital with or without established add-on treatment of potassium bromide or levetiracetam were treated add-on with imepitoin, starting at 10 mg/kg BID, with titration allowed to 30 mg/kg BID. In cohort B, the only difference to cohort A was that the starting dose of imepitoin was reduced to 5 mg/kg BID. In cohort C, animals not responding to imepitoin at >20 mg/kg BID were treated with phenobarbital add-on starting at 0.5 mg/kg BID. Results The add-on treatment resulted in a reduction in monthly seizure frequency (MSF) in all three cohorts. A reduction of ≥50% was obtained in 36-42% of all animals, without significant difference between cohorts. The lower starting dose of 5 mg/kg BID imepitoin was better tolerated, and an up-titration to on average of 15 mg/kg BID was sufficient in cohort A and B. In cohort C, a mean add-on dose of 1.5 mg/kg BID phenobarbital was sufficient to achieve a clinically meaningful effect. Six dogs developed a clinically meaningful increase in MSF of ≥ 50%, mostly in cohort A. Neither imepitoin nor phenobarbital add-on treatment was capable of suppressing cluster seizure activity, making cluster seizure activity an important predictor for drug-resistance. Conclusion A combination treatment of imepitoin and phenobarbital is a useful treatment option for a subpopulation of dogs with drug-resistant epilepsy, a low starting dose with 5 mg/kg BID is recommended.